Bimetal CuBO2 Fenton-like catalyst and preparation method thereof

The preparation of bimetallic CuBO2-type Fenton catalysts by hydrothermal method solved the problems of poor stability and low catalytic activity of existing iron-based catalysts, achieved the effect of efficient degradation of pollutants, and reduced the risk of pollution through magnetic recovery.

CN119819320AInactive Publication Date: 2025-04-15QINGDAO AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510051465.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing iron-based catalysts have problems of poor stability and low catalytic activity in advanced oxidation technology, and single metal catalysts are prone to cause heavy metal contamination during long-term use.

Method used

Bimetallic CuBO2 Fenton catalyst is prepared by hydrothermal method, and the redox reaction between metals such as manganese, iron, cobalt and copper is used to regulate the active sites of the catalyst and improve catalytic activity and stability.

Benefits of technology

The high activity and good chemical stability of the catalyst are achieved, the efficiency of catalytic degradation of pollutants is improved, and the catalyst can be recovered through magnets, reducing the risk of secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819320A_ABST
    Figure CN119819320A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite material preparation and water treatment, and provides a preparation method of a bimetallic CuBO2 Fenton-like catalyst, which comprises the following steps: mixing B salt (B = manganese, iron and cobalt), copper salt, water and strong alkali to obtain a bimetallic solution; the bimetallic solution is placed in a homogeneous reactor to be subjected to a hydrothermal reaction, and a bimetallic mixture is obtained; and adjusting the bimetallic mixture to be neutral by using dilute nitric acid, and drying to obtain the bimetallic CuBO2 Fenton-like catalyst. The bimetallic CuBO2 Fenton-like catalyst with high stability and high catalytic activity is prepared, the preparation method is a hydrothermal method, the condition is mild, operation is easy, the pollutant catalytic degradation effect is remarkable, stability is good, cost is low, the catalyst is suitable for industrial production and application, the preparation time can be shortened through the hydrothermal method, and the preparation cost is low. Therefore, the reaction rate is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation and water treatment, and in particular to a bimetallic CuBO2-type Fenton catalyst and a preparation method thereof. Background Art

[0002] Imidacloprid (IMI) is one of the most widely used insecticides in agriculture. As the first generation of neonicotinoid insecticides, it has a large residual amount in the environment. Although IMI is a low-toxic pesticide, studies have shown that while it has an effect on target organisms, it also has adverse effects on non-target organisms. Therefore, it is very important to take certain measures to reduce the exposure of IMI to the environment and human body. There are many ways to deal with water pollution caused by neonicotinoid pesticides: physical adsorption, biodegradation, chemical oxidation, etc. The advanced oxidation technology based on bimetallic copper iron ore has been widely used in the field of wastewater treatment because of its high efficiency, green environmental protection and good stability.

[0003] At present, the iron-based catalysts used in advanced oxidation technology are mainly single metal iron compounds, such as zero-valent iron (FeO), hematite (α-Fe2O3), magnetic hematite (γ-Fe2O3), magnetite (Fe3O4), goethite (α-FeO(OH)), pyrite (FeS2) and oxyferric chloride (FeOCl). The electron transfer at the interface of a single metal catalyst is slow, and the regeneration of the active metal on the catalyst surface cannot be achieved during the reaction, which limits the activity of the catalyst. By preparing multi-metal catalysts with different redox potentials, enhancing the electron transfer rate at the catalyst interface is an effective way to improve the activity of the catalyst. For example, transition metal ions (Mn, Fe, Co) as active sites can promote the reduction of Cu on the surface of copper-based catalysts through redox reactions with Cu. + The regeneration of the catalyst improves its ability to activate H2O2 to degrade pollutants. However, most metal oxides face the problem of metal ion leaching during the reaction process. The monocatalyst has poor stability when used for a long time and is prone to heavy metal pollution of water bodies. The copper-iron oxide (CuBO2, B = Mn, Fe, Co) with a good crystal structure contains Cu + It may exhibit better catalytic activity than iron-based catalysts and has the characteristics of stable resistance to interference from acids, alkalis, ions and other organic matter.

[0004] The physical and chemical properties of single metal iron-based catalysts are unstable and their catalytic activity is low. Most catalytic materials cannot be effectively recovered after degradation, which will cause secondary pollution to water bodies. When they are recovered later, the operating and treatment costs will be significantly increased. Summary of the invention

[0005] The present invention aims to provide a bimetallic CuBO2-type Fenton catalyst and a preparation method thereof, so that it has a high activity Cu + and good chemical stability, and metal B (Mn, Fe, Co) with different redox potentials from Cu can be used to regulate the components of CuBO2 active sites and cooperate with Cu.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a bimetallic CuBO2-type Fenton catalyst, comprising the following steps:

[0008] (1) Mixing B salt (B = manganese, iron, cobalt), copper salt, water and strong base to obtain a bimetallic solution;

[0009] (2) placing the bimetallic solution in a homogeneous reactor for hydrothermal reaction to obtain a bimetallic mixture;

[0010] (3) adjusting the bimetallic mixture to neutrality with dilute nitric acid and then drying it to obtain the bimetallic CuBO2-type Fenton catalyst;

[0011] In the step (1), the salt B is one of a manganese salt, an iron salt or a cobalt salt.

[0012] Furthermore, the manganese salt is one or more of manganese chloride, manganese sulfate and manganese nitrate;

[0013] The iron salt is one or more of ferric chloride, ferric sulfate solution and ferric nitrate solution;

[0014] The cobalt salt is one or more of cobalt chloride, cobalt sulfate and cobalt nitrate;

[0015] The copper salt is one or more of copper sulfate, copper chloride, copper nitrate or copper carbonate;

[0016] In the step (1), the strong base is sodium hydroxide.

[0017] Furthermore, in step (1), the molar ratio of the metal ions in the B salt to the copper ions in the copper salt is 0.8-1.2:0.8-1.2;

[0018] The volume molar ratio of water to copper salt in step (1) is 40-80 mL:10-20 mmol;

[0019] In the step (1), the mass volume ratio of the strong base to water is 3-6 g:40-80 mL.

[0020] Furthermore, when the B salt in step (1) is an iron salt, ethylene glycol solution needs to be added.

[0021] Furthermore, the mass fraction of the ethylene glycol solution is 90-98%;

[0022] The volume ratio of the ethylene glycol solution to the water in step (1) is 1.5-3 mL:40-80 mL.

[0023] Furthermore, the temperature of the hydrothermal reaction in step (2) is 150-200°C;

[0024] The hydrothermal reaction time is 12 to 24 hours.

[0025] Furthermore, the concentration of the dilute nitric acid in step (3) is 0.8 to 1.2 mmol / L.

[0026] Furthermore, the drying temperature in step (3) is 60 to 80°C;

[0027] The drying time is 6 to 8 hours.

[0028] The present invention also provides a bimetallic CuBO2 Fenton catalyst obtained by a method for preparing a bimetallic CuBO2 Fenton catalyst.

[0029] The present invention also provides an application of a bimetallic CuBO2-type Fenton catalyst in treating sewage.

[0030] The present invention has the following beneficial effects:

[0031] (1) The present invention prepares a bimetallic CuBO2-type Fenton catalyst with strong stability and catalytic activity. The preparation method of the present invention is a hydrothermal method, which has mild conditions, simple operation, significant catalytic degradation effect of pollutants, good stability and low cost, and is suitable for industrial production and application. The hydrothermal method of the present invention can shorten the preparation time, which greatly improves the reaction rate.

[0032] (2) The product prepared by the present invention is a CuBO2 bimetallic catalytic material. The interaction between metal ions can increase the electron transfer rate on the catalytic surface and generate more active sites, thereby improving the catalytic activity.

[0033] (3) The product prepared by the present invention is a magnetic material. In the process of photocatalytic treatment of wastewater, it is very necessary to recover the catalyst after the reaction is completed to avoid secondary pollution of the water body. The composite material can be effectively recovered by an external magnet, thereby improving the recycling of the catalyst.

[0034] (4) The bimetallic CuBO2-type Fenton catalyst prepared by the present invention can expose more active sites, Cu + As a transition metal ion, it can promote B through a spontaneous redox process 2+Regeneration, B 2+ The ·OH produced by the reaction with H2O2 can oxidize and degrade various toxic and difficult-to-biodegrade organic matter, thereby achieving the purpose of removing pollutants and making the catalyst exhibit higher catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 XRD diffraction patterns of bimetallic CuBO2-type Fenton catalysts of Examples 1 to 3;

[0036] Figure 2 The SEM images of the bimetallic CuBO2-type Fenton catalysts of Examples 1 to 3;

[0037] Figure 3 The diagram shows the degradation effect of the bimetallic CuBO2-type Fenton catalyst of Examples 1 to 3 on imidacloprid in the imidacloprid solution. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing a bimetallic CuBO2-type Fenton catalyst, comprising the following steps:

[0039] (1) Mixing B salt (B = manganese, iron, cobalt), copper salt, water and strong base to obtain a bimetallic solution;

[0040] (2) placing the bimetallic solution in a homogeneous reactor for hydrothermal reaction to obtain a bimetallic mixture;

[0041] (3) adjusting the bimetallic mixture to neutrality with dilute nitric acid and then drying it to obtain the bimetallic CuBO2-type Fenton catalyst;

[0042] In the present invention, the salt B in step (1) is one of a manganese salt, an iron salt or a cobalt salt.

[0043] B 3+ +3OH - =B(OH)3 (1)

[0044] B(OH)3=B2O3+3H2O (2)

[0045] Cu 2+ +2OH - =Cu(OH)2 (3)

[0046] 2Cu(OH)2+2e - =Cu2O+2OH - +H2O (4)

[0047] Cu2O+B2O3=2CuBO2 (5)

[0048] In the present invention, the B salt and the copper salt are first dissolved in water and stirred, and then a strong base is added and mixed to obtain a bimetallic solution.

[0049] In the present invention, the manganese salt is preferably one or more of manganese chloride, manganese sulfate and manganese nitrate.

[0050] In the present invention, the iron salt is preferably one or more of ferric chloride, ferric sulfate and ferric nitrate.

[0051] In the present invention, the cobalt salt is preferably one or more of cobalt chloride, cobalt sulfate and cobalt nitrate.

[0052] In the present invention, the copper salt is preferably one or more of copper sulfate, copper chloride, copper nitrate or copper carbonate.

[0053] In the present invention, the strong base in step (1) is preferably sodium hydroxide.

[0054] In the present invention, the stirring rate is preferably 100 to 300 r / min, more preferably 120 to 280 r / min, and more preferably 150 to 250 r / min.

[0055] In the present invention, the stirring time is preferably 10 to 30 min, more preferably 12 to 28 min, and even more preferably 15 to 25 min.

[0056] In the present invention, the molar ratio of the metal ions in the B salt to the copper ions in the copper salt in step (1) is preferably 0.8-1.2:0.8-1.2, more preferably 0.9-1.1:0.9-1.1, and more preferably 1:1.

[0057] In the present invention, the volume molar ratio of water to copper salt in step (1) is preferably 40-80 mL:10-20 mmol, more preferably 45-75 mL:12-18 mmol, and more preferably 50-70 mL:14-16 mmol.

[0058] In the present invention, the mass volume ratio of the strong base to water in step (1) is preferably 3-6 g:40-80 mL, more preferably 3.5-5.5 g:45-75 mL, and more preferably 4-5 g:50-70 mL. In the present invention, when the B salt in step (1) is an iron salt, ethylene glycol solution is also added.

[0059] In the present invention, the mass fraction of the ethylene glycol solution is preferably 90 to 98%, more preferably 92 to 98%, and even more preferably 95 to 98%.

[0060] In the present invention, the volume ratio of the ethylene glycol solution to the water in step (1) is preferably 1.5-3:40-80, more preferably 2-3:45-75; more preferably 2-2.5:50-70.

[0061] In the present invention, the temperature of the hydrothermal reaction in step (2) is preferably 150-200°C, more preferably 160-190°C, and even more preferably 170-180°C.

[0062] In the present invention, the hydrothermal reaction time is preferably 12 to 24 hours, more preferably 14 to 22 hours, and even more preferably 16 to 20 hours.

[0063] In the present invention, the bimetallic mixture needs to be washed with dilute nitric acid, water and anhydrous ethanol in sequence until it becomes neutral to remove impurities, and then dried under a vacuum environment.

[0064] In the present invention, the concentration of the dilute nitric acid in step (3) is preferably 0.8 to 1.2 mmol / L, more preferably 0.9 to 1.1 mmol / L, and more preferably 1.0 mmol / L.

[0065] In the present invention, the number of washing is preferably 1 to 6 times, more preferably 2 to 5 times, and even more preferably 3 to 4 times.

[0066] In the present invention, the drying temperature in step (3) is preferably 60 to 80°C, more preferably 62 to 78°C, and even more preferably 65 to 75°C.

[0067] In the present invention, the drying time is preferably 6 to 8 hours, more preferably 6.2 to 7.8 hours, and even more preferably 6.5 to 7.5 hours.

[0068] In the present invention, the dried product needs to be ground to obtain the bimetallic CuBO2 Fenton catalyst.

[0069] In the present invention, the average particle size of the bimetallic CuBO2-based Fenton catalyst is 25 to 150 μm, more preferably 50 to 125 μm, and even more preferably 75 to 100 μm.

[0070] The present invention also provides a bimetallic CuBO2 Fenton catalyst obtained by a method for preparing a bimetallic CuBO2 Fenton catalyst.

[0071] The present invention also provides an application of a bimetallic CuBO2-type Fenton catalyst in treating sewage.

[0072] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0073] Example 1

[0074] 15 mmol of copper nitrate and 15 mmol of manganese chloride solution were weighed and dissolved in 60 mL of water in a ratio of 1:1. After stirring at a rate of 200 r / min for 30 min, 4.4 g of sodium hydroxide was added and mixed for 10 min until uniform dispersion to obtain a bimetallic solution. The bimetallic solution was placed in a homogeneous reactor, subjected to a hydrothermal reaction at 180° C. for 12 h, and then cooled to room temperature to obtain a bimetallic mixture. The bimetallic mixture was washed three times with 1.0 mmol / L dilute nitric acid, water and anhydrous ethanol until neutral, and then placed in a vacuum drying oven, dried at 60° C. for 8 h, and then ground to obtain a bimetallic CuMnO2 Fenton catalyst with an average particle size of 25 μm.

[0075] Example 2

[0076] 15 mmol of copper nitrate and 15 mmol of ferric nitrate were weighed and dissolved in 60 mL of water in a ratio of 1:1. After stirring at a rate of 200 r / min for 30 min, 4.4 g of sodium hydroxide was added and mixed for 10 min until uniform dispersion was achieved. Then, 2 mL of ethylene glycol solution with a mass fraction of 98% was added and mixed uniformly to obtain a bimetallic solution. The bimetallic solution was placed in a homogeneous reactor, subjected to a hydrothermal reaction at 180° C. for 12 h, and then cooled to room temperature to obtain a bimetallic mixture. The bimetallic mixture was washed three times with 1.0 mmol / L dilute nitric acid, water and anhydrous ethanol until neutral, and then placed in a vacuum drying oven, dried at 60° C. for 8 h, and then ground to obtain a bimetallic CuFeO2 Fenton catalyst with an average particle size of 100 μm.

[0077] Example 3

[0078] 15 mmol of copper nitrate and 15 mmol of cobalt nitrate were weighed and dissolved in 60 mL of water in a ratio of 1:1. After stirring at a rate of 200 r / min for 30 min, 4.4 g of sodium hydroxide was added and mixed for 10 min until uniform dispersion to obtain a bimetallic solution. The bimetallic solution was placed in a homogeneous reactor, subjected to hydrothermal reaction at 180°C for 12 h, and then cooled to room temperature to obtain a bimetallic mixture. The bimetallic mixture was washed three times with 1.0 mmol / L dilute nitric acid, water and anhydrous ethanol until neutral, and then placed in a vacuum drying oven, dried at 60°C for 8 h, and then ground to obtain a bimetallic CuCoO2 Fenton catalyst with an average particle size of 150 μm.

[0079] Effect test:

[0080] The catalysts prepared in Examples 1 to 3 were tested by X-ray diffractometer. Figure 1 shown.

[0081] from Figure 1 It can be seen that the diffraction peak of CuMnO2 prepared in this application has a good correspondence with the typical CuMnO2 phase (JCPDS No.50-0860).

[0082] The diffraction peaks of CuFeO2 have a good correspondence with the typical CuFeO2 phase (JCPDS No.85-0605).

[0083] The diffraction peaks of CuCoO2 have a good correspondence with the typical CuCoO2 phase (JCPDS No.74-1855).

[0084] The catalysts prepared in Examples 1 to 3 were observed by scanning electron microscopy. Figure 2 As shown, (a) is CuMnO2, (b) is CuFeO2, and (c) is CuCoO2.

[0085] from Figure 2 It can be seen that there are many small particles distributed on the surface of CuBO2 prepared in this application, which can expose more active sites.

[0086] A 5 mg / L imidacloprid solution was prepared and loaded into a 100 mL reactor. 20 mg of each of the three bimetallic Fenton catalysts obtained in Examples 1 to 3 were weighed and added to the 5 mg / L imidacloprid solution. Then, 50 mmol / L of 30% H2O2 solution was slowly added with a pipette while stirring to uniformly mix the reaction system. Samples were taken from three beakers for analysis. The residual concentration of imidacloprid was determined by high performance liquid chromatography. The degradation effect was as follows: Figure 3 shown.

[0087] from Figure 3 It can be seen that the degradation efficiency of imidacloprid in water by activating H2O2 using the three catalysts CuMnO2, CuFeO2 and CuCoO2 prepared in this application is higher than 90%.

[0088] As can be seen from the above embodiments, the present invention provides a method for preparing a bimetallic CuBO2-type Fenton catalyst, comprising the following steps: mixing B salt (B = manganese, iron, cobalt), copper salt, water and strong base to obtain a bimetallic solution; placing the bimetallic solution in a homogeneous reactor for hydrothermal reaction to obtain a bimetallic mixture; adjusting the bimetallic mixture to neutrality with dilute nitric acid, and drying to obtain the bimetallic CuBO2-type Fenton catalyst. The present invention prepares a bimetallic CuBO2-type Fenton catalyst with strong stability and strong catalytic activity. The preparation method of the present invention is a hydrothermal method, which has mild conditions, simple operation, significant catalytic degradation of pollutants, good stability and low cost, and is suitable for industrial production and application. The preparation time can be shortened by the hydrothermal method of the present invention, which greatly improves the reaction rate. The product prepared by the present invention is a CuBO2 bimetallic catalytic material, and the interaction between metal ions can increase the electron transfer rate on the catalytic surface and produce more active sites. Thereby, the catalytic activity is improved. The product prepared by the present invention is a magnetic material. In the process of photocatalytic treatment of wastewater, it is very necessary to recover the catalyst after the reaction is completed to avoid secondary pollution of the water body. The composite material can be effectively recovered by an external magnet, thereby improving the recycling of the catalyst. The bimetallic CuBO2 Fenton catalyst prepared by the present invention can expose more active sites. + As a transition metal ion, it can promote B through a spontaneous redox process 2+ Regeneration, B 2+ The ·OH produced by the reaction with H2O2 can oxidize and degrade various toxic and difficult-to-biodegrade organic matter, thereby achieving the purpose of removing pollutants and making the catalyst exhibit higher catalytic activity.

[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a bimetallic CuBO2-type Fenton catalyst, characterized in that: The following steps are involved: (1) dissolving B salt (B = manganese, iron, cobalt), copper salt, water and strong base to obtain a bimetallic solution; (2) placing the bimetallic solution in a homogeneous reactor for hydrothermal reaction to obtain a bimetallic mixture; (3) adjusting the bimetallic mixture to neutrality with dilute nitric acid and then drying it to obtain the bimetallic CuBO2-type Fenton catalyst; In the step (1), the salt B is one of a manganese salt, an iron salt or a cobalt salt.

2. The preparation method according to claim 1, characterized in that: The manganese salt is one or more of manganese chloride, manganese sulfate and manganese nitrate; The iron salt is one or more of ferric chloride, ferric sulfate and ferric nitrate; The cobalt salt is one or more of cobalt chloride, cobalt sulfate and cobalt nitrate; The copper salt is one or more of copper sulfate, copper chloride, copper nitrate and copper carbonate; In the step (1), the strong base is sodium hydroxide.

3. The preparation method according to claim 1, characterized in that: In the step (1), the molar ratio of the metal ions in the B salt to the copper ions in the copper salt is 0.8-1.2:0.8-1.2; The volume molar ratio of water to copper salt in step (1) is 40-80 mL:10-20 mmol; In the step (1), the mass volume ratio of the strong base to water is 3-6 g:40-80 mL.

4. The preparation method according to claim 1, characterized in that: When the B salt in step (1) is an iron salt, ethylene glycol solution needs to be added.

5. The preparation method according to claim 4, characterized in that: The mass fraction of the ethylene glycol solution is 90-98%; The volume ratio of the ethylene glycol solution to the water in step (1) is 1.5-3:40-80.

6. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 150-200° C.; The hydrothermal reaction time is 12 to 24 hours.

7. The preparation method according to claim 1, characterized in that: The concentration of dilute nitric acid in step (3) is 0.8-1.2 mmol / L.

8. The preparation method according to claim 1, characterized in that: The drying temperature in step (3) is 60-80°C; The drying time is 6 to 8 hours.

9. A bimetallic CuBO2 Fenton catalyst obtained by the preparation method of a bimetallic CuBO2 Fenton catalyst according to any one of claims 1 to 8.

10. Use of a bimetallic CuBO2-type Fenton catalyst as claimed in claim 9 in treating sewage.

Citation Information

Patent Citations

  • Heterogeneous photo-Fenton catalyst with copper and iron dual-Fenton active elements as well as preparation method and application of heterogeneous photo-Fenton catalyst

    CN116809093A